Eliminating "Us and Them" Using IT Governance, Process, and Behavioral Management to Make it and the Business One - Romero, Steven; SpringerLink (Online service). (New York Distributed by Springer-Verlag, 2011)
Discusses ways in which IT departments can responsibly align themselves with the core values of their company, manage resources and performance, and minimize risk to deliver added value to business objectives and profitability.
Electronic reproduction.
Keywords: Information technology -- Management; Industrial organization; Electronic books